ANALISIS KINERJA KEUANGANDILIHAT DARI CURRENT RATIO, DEBT TO EQUITY RATIO, DAN RETURN ON ASSETS PADA KOPERASI WANITA “SALIMA” KECAMATAN TUGUMULYOKABUPATEN MUSI RAWAS - Surajiyo Surajiyo (Jurnal Media Ekonomi (JURMEK), 2018)
This study aims to determine financial performance. Based on the Regulation of the State Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 20 / Per / M.KUKM / XI / 2008. The type of research conducted by descriptive quantitative. The data sources used are secondary data derived from financial statements in the form of balance sheets and profit and loss between 2012-2016. The data analysis technique in this study uses quantitative analysis, namely analyzing financial statements with a ratio approach, namely the current ratio, debt to equity ratio, and return on assets, then adjusted to the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 20 / Per / M .KUKM / XI / 2008. The results showed that based on the Regulation of the State Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 20 / Per / M.KUKM / XI / 2008 "SALIMA" Women's Cooperative in Tugumulyo District, Musi Rawas Regency for five years from 2012-2016 seen from the Current Ratio including the unhealthy category. Thus the "SALIMA" Women's Cooperative is unable to pay its short-term obligations. Whereas based on the Debt to Equity Ratio from 2012 to 2016 included in the category of unhealthy. Thus indicating that the cooperative capital condition is insufficient to guarantee the debt given by the creditor. While based on On Asset Returns from 2012 to 2016 included in the category of being less healthy. Thus cooperatives are less able to manage their assets so as to produce unhealthy profits.